Dynamic Changes in Coagulation Function in Patients With Pneumonia Under Admission and Non-admission Treatment - Xu, Jiasheng; Zhang, Yongmei; Li, Yiran; Liao, Kaili; Zeng, Xiong; Zeng, Xiande; Meng, Rui; Zhou, Weimin; Wang, Kai; Gong, Yuanqi; Hua, Fuzhou; Xu, Jianjun; et al. (Frontiers in Medicine, 2021)
Objective: To explore the dynamic changes of coagulation function and the effect of age on the results of coagulation function in patients with pneumonia under admission and non-admission treatment. Methods：We included 178 all confirmed adult inpatients with COVID 19 from Wuhan Union Hospital Affiliated to Huazhong University of Science and Technology (Wuhan, China). The patients were divided into four groups according to the time from the first symptom onset to hospital admission for comparative analysis; the patients who were admitted within two weeks of the onset of disease were analyzed for the dynamic changes of their blood coagulation test. A group of patients admitted to the hospital within two weeks after the onset of disease and another group of patients admitted to the hospital after two weeks were further divided into two groups based on whether they were over 55 years of age. Chi-square test and T test were used to explore the dynamic changes of coagulation function and the influence of age factors on the results of coagulation function test. Results：178 inpatients were included in this analysis, 34 of them were under dynamic detection. We divided these patients into four groups according to the interval between the onset of COVID-19 pneumonia and the time being admitted to hospital: 1-7 day group (group 1), 8-14 day group (group 2), 15-21 day group (group 3), >21 day group (group 4). After being admitted to hospital, the most significant decrease of 8 factors was between week two and week three. The 8 factors had distinct differences between people older than 55 and those younger than 55. In the first two weeks after being admitted, the level of 8 factors in patients >55 were significantly higher than patient <55; and after another two weeks of treatment, the factors level in both age group back to normal. Conclusion：Eight factors all increased within two weeks after the onset, and gradually decreased to normal after two weeks no matter undergoing treatment or not. Compared with patients younger than 55 years, patients older than 55 years have greater changes in their blood coagulation test values.